Major Metabolites of Methylripariochromene-A, a Bioactive Substance in The Leaves of Eupatorium Riparium Reg. in Male Rats Urine - Subagus Wahyuono; Charles S. Vairappan; Datin Maryati Mohd.; Vera Fauziati; Purwantiningsih Purwantiningsih; Marchaban Marchaban (Majalah Farmaseutik, 2018)
Methylripariochromene-A (MRC) (1) is the principal bioactive compound isolated from Eupatorium riparium Reg. collected from the Mt. Merapi National Park. MRC was isolated from the chloroform extract of the leaves by using bioassay (BST) guided isolation method. MRC causes diuretic, reduces the blood pressure and excretes mineral from the body. This activity is comparable to a clinically used diuretic drug, furosemide. MRC is a chromene type of compound, having 2 –OCH3 groups on the aromatic ring that are possibly demethylated in vivo to give phenolic compounds well known for having antiseptic properties. This study was aimed to evaluate diuretic properties compared to furosemide, isolate and identify MRC major metabolites present in urine. If it is true, then MRC probably can be used also as anti-infectious diseases in the tractus urinary. n-Hexane extract (81% MRC) of E. riparium (1.25 g/kg bw) was applied p.o on male rats (+ 200g) and furosemide was used as a positive control of diuretic activity. Urine was collected during 48 hours, partitioned with EtOAc for 15 minutes to give EtOAc fraction at the upper layer. The EtOAc fraction was then checked by tlc with MRC as the reference standard. The major metabolites were isolated by fractionating the EtOAc fraction followed by purification using preparative tlc (fr. 4-5 and 6-7). The major metabolites obtained were identified based on their 1H- and 13C-NMR data. Diuretic effect of n-hexane extract (1.25 g/kg bw) was comparable to furosemide (8.83 mL/rat vs 8.70 mL/rat for 24 hours). The 1H- and 13C-NMR data of fr 4-5 indicated that there was not major changing in the 1H- and 13C-NMR spectra appearance compared to that of MRC, except that 1 –OCH3 group was demethylated became demethyl MRC (2) . Based on HMBC and HMQC experiments, -OCH3 at C-8 was the one demethylated. The 1H-NMR data of fr. 6-7 was similar to fr. 4-5, demethylation of one –OCH3 group on C-8 but the ether linkage in the furan ring system was broken to give 2 tentative structures (3 and 4).